B4C-based nanoenhancement on the thermophysical and stability performance of solar salt: a novel approach for high-temperature TES applications - Gurgenc, Ezgi; Öztop, Hakan Fehmi; Yamac, Halil ibrahim; Canbay, Canan Aksu; Senocak, Safak Melih; Ozabaci, Murat; Gur, Muhammed (Elsevier, 2025)
Enhancement of the thermophysical properties of molten salt-based nanofluids is essential for improving energy density and efficiency in high-temperature thermal energy storage (TES) systems. However, the mechanisms behind the anomalous increase in specific heat capacity upon nanoparticle addition remain unclear. In this study, solar salt (60 wt% NaNO3-40 wt% KNO3) was modified with boron carbide (B4C) nanoparticles at concentrations of 0.5, 1.0, 1.5, and 2.0 wt% using a wet dispersion method. The structural and thermal behaviors of the nanofluids were investigated through X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), field emission scanning electron microscopy with energy-dispersive X-ray spectroscopy (FE-SEM/ EDX), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The DSC results from the second thermal cycle confirmed that the addition of B4C significantly enhanced the Cp of the base salt. Specifically, the 2.0 wt% B4C sample exhibited average enhancements of 31.5 % in the solid phase (100-220 degrees C) and 49.83 % in the liquid phase (250-400 degrees C) compared to pure solar salt, with a peak value of 2.11 J/g.K at 250 degrees C. FE-SEM analyses revealed more uniform nanoparticle distribution at lower concentrations, while higher loadings led to particle agglomeration. Thermal conductivity increased by 142.8 %, from 1.05 to 2.55 W/m.K. Although latent heat decreased with higher nanoparticle content (from 108.7 J/g to 97.2 J/g), thermal stability improved, with the decomposition onset temperature shifting from 607 degrees C to 644 degrees C at 1.5 wt% B4C. These results identify B4C as a promising non-oxide nanoadditive for TES applications, offering balanced improvements in thermal performance and stability.
Keywords: Boron carbide; Solar salt; Specific heat capacity; Thermal conductivity; Concentrated solar power; Thermal energy storage